Using Telepractice to Deliver Pediatric Voice Care in a Changing World: Breaking down Challenges and Learning from Successes - Kelchner, Lisa N.; Fredeking, John C., II; Zacharias, Stephanie Cotton (Seminars in Speech and Language, 2021)
For children with voice disorders, access to care has long been a challenge. Reasons for this include the challenge of qualifying children with isolated voice disorders for services within the public-school system as well as a family's geographic proximity to experienced clinicians who are in the healthcare system. Over the past decade, there have been both formal and informal investigations into the use of telepractice to deliver services to communicatively disordered children and adults, including those with voice disorders. Although barriers and obstacles existed, use of telepractice to deliver such services demonstrated both feasibility and, in some studies, effective outcomes. However, prior to spring of 2020, use of telepractice to deliver speech pathology services was not mainstream. This changed when the nation was forced to shut down many of its in-person healthcare and educational delivery due to the COVID-19 pandemic. This article summarizes select relevant literature pertaining to the use of telepractice in speech language pathology over the past decade and provides a case-based discussion of how it was and is currently being used to deliver pediatric voice care.
Keywords: pediatric voice; dysphonia; voice therapy; telepractice; pandemic healthcare